Essential Oil and Fatty Acid Composition of Centaurea solstitialis ssp. solstitialis - Burcu Sumer Tuzun; Tuba Gonenc; Pelin Tastan; Tugce Fafal; Betul Demirci (International Journal of Secondary Metabolite)
Centaurea is a widespread genus from Asteraceae family in Turkey. There are plenty of researches about fatty acid and essential oil profiles of Centaurea species. Essential oils were obtained using a Clevenger apparatus by hydrodistillation from aerial part of the plant. The essential oil composition of the plant was identified by GC-MS using FID detector. 31 compounds representing 91.5% were identified. Hexadecanoic acid (50.2%) and tetradecanoic acid (10.1%) were found to be the major compounds. For fatty acids, fatty acid methyl esters (FAMEs) were prepared. The fatty acid compositions were analyzed by GC. Saturated fatty acids (SFAs) were totally 25.05%, monounsaturated fatty acids (MUFAs) were 19.60% and polyunsaturated fatty acids were 19.86%. The major compounds were found as oleic acid (18.54%), linoleic acid (10.07%), palmitic acid (8.28%), stearic acid (6.82%) and ℽ- linoleic acid (6.75%).